Modifikasi Algoritma Controlling Expansion Dalam Meningkatan Kapasitas Penyisipan Data Hiding: Modification of the Controlling Expansion Algorithm Increasing Hiding Data Insertion Capacity - kristoforus Fallo (Department of Information Technology, Universitas Timor, Indonesia, 2022)
Stegonography is the art of hiding messages in other media. Stegonography is widely used to send secret messages without being known by other people by using digital media in the form of image files so that besides the sender and recipient no one knows or is aware that there is a secret message in it. Several researchers have developed these methods such as Difference Expansion, Reduced Difference Expansion, Quad Difference Expansion and Controlling Expansion. These methods have been able to recover and improve data embedding but during the running process there are several problems that often occur, namely overflow and underflow of pixel values. To overcome the above problems, we modify the Controlling Expansion algorithm by minimizing the condition of the pixel difference value and reducing the final pixel difference value after inserting the data bit and using the Location Map on the new pixel value and during secret data extraction. The experimental results show that the proposed method can increase the data storage capacity and the PSNR of stego images is higher than the previous method.